2023
DOI: 10.3390/molecules28145616
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Antagonizes the Sedative Effects of Linalool, Possibly through the GABAergic Interaction Pathway

Mehedi Hasan Bappi,
Abdullah Al Shamsh Prottay,
Hossam Kamli
et al.

Abstract: Sedatives promote calmness or sleepiness during surgery or severely stressful events. In addition, depression is a mental health issue that negatively affects emotional well-being. A group of drugs called anti-depressants is used to treat major depressive illnesses. The aim of the present work was to evaluate the effects of quercetin (QUR) and linalool (LIN) on thiopental sodium (TS)-induced sleeping mice and to investigate the combined effects of these compounds using a conventional co-treatment strategy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…The stereochemical characteristics of the predicted models of the GABA protein were confirmed by uploading PDB files to the PDBsum site and having the PROCHECK program examine them. The Phi/Psi Ramachandran plot from the PROCHECK site verified the stereochemical characteristics of the predicted model GABA protein (Bappi, Prottay, Kamli, et al, 2023; Yadav et al, 2013).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…The stereochemical characteristics of the predicted models of the GABA protein were confirmed by uploading PDB files to the PDBsum site and having the PROCHECK program examine them. The Phi/Psi Ramachandran plot from the PROCHECK site verified the stereochemical characteristics of the predicted model GABA protein (Bappi, Prottay, Kamli, et al, 2023; Yadav et al, 2013).…”
Section: Resultsmentioning
confidence: 53%
“…Furthermore, SCL (5, 10, and 15 mg/kg) inhibitory‐like effect on emetic chicks (Bappi, Prottay, Al‐Khafaji, et al, 2023). Several investigations have found that QR (50 and 100 mg/kg) has a strong antidepressant effect in a mouse model (Anjaneyulu et al, 2003; Bappi, Prottay, Kamli, et al, 2023). In addition, DZP (1–3 mg/kg) is often used as a standard treatment for studying sedative, hypnotic, anxiolytic, and other effects on rats and mice (Bappi, Prottay, Kamli, et al, 2023; Iwashita et al, 2023; Meneses et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy minimization of the ligand structures was performed using the MM2 force field in Chem3D software (version Pro21.0 PerkinElmer Informatics, Inc., Boston, MA, United States) ( Akbor et al, 2023a ). Finally, DPL structure was validated using Lipinski’s rule of five and ADMET analysis in the SwissADME online tool ( Bappi et al, 2023b ). This ensured that the ligands had favorable pharmacological properties and were suitable for molecular docking studies with the prepared protein structures.…”
Section: Methodsmentioning
confidence: 99%